Determinants of natural gas demand in Ghana. (September 2014) - Ackah, Ishmael
Abstract The study investigates the effect of economic and non‐economic factors on natural gas demand in Ghana at the aggregate and disaggregates levels. The structural time series model is employed as it has the ability of capturing exogenous non‐economic factors. The findings suggest that both economic and non‐economic factors influence natural gas demand. It further reveal that different sectors respond differently to these factors. The study recommends that policies such as natural gas price subsidies should be customised for different sectors to obtain optimal results.